Shrek 2 - Adamson, Andrew; Asbury, Kelly; Warner, Aron; DreamWorks Pictures (1994-2006) (Madrid : DreamWorks Home Entertainment ; Twentieth Century Fox Home Entertainment, 2009)
The ogre Shrek and his new bride, Princess Fiona, return from their honeymoon to find a dinner invitation from Fiona's parents. The only problem is that the unsuspecting parents have no idea that their daughter and her husband are ogres.
Originally released as a motion picture in 2004.
Based on the story by Andrew Adamson, based on the book by William Steig.
Executive producer, Jeffrey Katzenberg; editors, Michael Andrews, Sim Evan-Jones; music, Harry Gregson-Williams; production design, Guillaume Aretos.
Voices: Mike Myers, Eddie Murphy, Cameron Diaz, Julie Andrews, Antonio Banderas, John Cleese, Rupert Everett, Jennifer Saunders.
General audience.
DVD, region 2; widescreen, aspect ratio 1.85:1; Dolby digital 5.1.
Keywords: Ghouls and ogres -- Drama; Ugliness -- Drama; Computer animation films; Comedy films; Fiction films; Feature films